Smart Car parking System using Arduino controller - Mrs.Deva priya .S, Mr.Sundar.R, Dr.M.Deva Brinda (International Journal of Advanced Science and Technology, 2020)
The Smart system is to monitor and count the number of automobiles entering and leaving a parking, open the gate for authorized personnel, provide information about free parking spaces, create data base to provide statistics about people entering and leaving the parking space. This system connected to the web server which updates the real time count of vacant area. The parking guidance system presents a unique method of vehicle detection using an ultrasonic sensor. This system uses efficient sensors and display circuits to withstand the surrounding environment.